Analisis Penerapan Cost-Volume-Profit (CVP) pada Perencanaan Laba di Alma Network Solution - Elsa Wantira; Rizky Ridwan; Retno Dyah Pekerti (BADAN PENERBIT STIEPARI PRESS, 2026)
This study aims to analyze the application of cost-volume-profit (CVP) analysis as a profit planning tool at Alma Network Solution, a micro, small, and medium enterprise (MSME) providing internet services. The research method used is descriptive quantitative with a case study approach. The results show that in 2024, the company generated a contribution margin of IDR 58,343,314. The breakeven point was calculated at 1,320 customers, equivalent to IDR 170,087,380. The company’s margin of safety was recorded at -14%, indicating that actual sales in 2024 were not sufficient to cover the breakeven point. To achieve the expected profit, the company needs to reach a sales target of approximately 1,132 customer payments, or IDR 175,467,975 in total sales. Meanwhile, based on the CVP analysis, for a company experiencing losses, it is more advisable to focus on reaching the breakeven point without setting a specific profit target. In this case, the sales target to reach breakeven is IDR 191,609,760, equivalent to 1,488 customer payments. The conclusion of this analysis provides a basis for the company to plan its sales targets more optimally for profit planning, ensuring business sustainability in the coming year.